2020
DOI: 10.1108/etpc-11-2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Tuning into rebellious matter: affective literacies as more-than-human sonic bodies

Abstract: Purpose The purpose of this article is to explore the sonic vibrations, infectious rhythms, and alternative frequencies that are often unheard and overlooked within mainstream educational spaces–that is, perceptually coded out of legibility by those who read/see/feel/hear the world through “whiteness.” Design/methodology/approach “Plugging into” (Jackson and Mazzei, 2012) posthuman theories of affect (Deleuze and Guattari, 1987; Henriques, 2010) and assemblage (Weheliye, 2014), the author argues that “litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…This understanding of young children's vocalisations as joining in with a place or a soundscape coheres with other research that has demonstrated the influence of place on children's talk (Arculus and MacRae, 2020; Dean, 2021; Hackett et al, 2021; Heath, 1983; Richardson and Murray, 2017) and the importance of bodies and movement for young children's meaning making (Daniels, 2016; Dernikos, 2020; Flewitt, 2005; Hackett, 2014; Powell and Somerville, 2018; Thiel, 2015). A more‐than‐human understanding of young children's talk extends this work by rethinking the tendency to separate out place from body and see the one acting on or influencing the other.…”
Section: Language In/of Placesupporting
confidence: 85%
See 1 more Smart Citation
“…This understanding of young children's vocalisations as joining in with a place or a soundscape coheres with other research that has demonstrated the influence of place on children's talk (Arculus and MacRae, 2020; Dean, 2021; Hackett et al, 2021; Heath, 1983; Richardson and Murray, 2017) and the importance of bodies and movement for young children's meaning making (Daniels, 2016; Dernikos, 2020; Flewitt, 2005; Hackett, 2014; Powell and Somerville, 2018; Thiel, 2015). A more‐than‐human understanding of young children's talk extends this work by rethinking the tendency to separate out place from body and see the one acting on or influencing the other.…”
Section: Language In/of Placesupporting
confidence: 85%
“…Posthuman and post-qualitative research in recent years have acted as gathering points for a growing critique of the assumption that 'human' is a fixed and unproblematic category (Braidotti, 2013) and a related interest in what kinds of knowledge qualitative research methods privilege or surface (MacLure, 2013). Implications for educational research include the need to consider young people beyond the confines of the bounded individual, seeing instead how any one child is deeply inter-connected not just to other humans but to the more-than-human context in which they are learning or acting (Dernikos et al, 2020;Taylor and Hughes, 2016). Human bodies themselves are not bounded; host to multiple other beings that influence our well-being and thought processes, the human body, in this sense, is itself more-than-human (Alaimo, 2010).…”
Section: Studying the Emergence Of Language Through Community Ethnogr...mentioning
confidence: 99%
“…Dyson, 2003, 2008; Henning, 2019; Kontovourki & Siegel, 2022). Focusing particularly on children's talk and noise in an early primary classroom, Dernikos (2020) suggested that the regulation of sounds cites hegemonic, raced and classed discourses but is never fixed. As she pointed out, in mainstream educational spaces, certain sounds (noises coming from outside the classroom, unsanctioned student talk, out‐of‐turn talking) were coded out or policed, at the same time that it was also possible for children to resist such policing and regulation.…”
Section: Talk Discourse and Noise In Schooled Bodiesmentioning
confidence: 99%
“…To emphasise this possibility of the concurrent emergence, hence vibrancy, and boundedness, hence stillness, of literacy learning, researchers have suggested that forces affectively vibrate together (Dernikos, 2020); that intra‐active encounters of human and nonhuman bodies are vibrant and in motion (Wargo, 2018); that one's own body may be seen as vibrant matter (Thiel, 2016). Across these studies, action is dispersed in the entanglements of material entities, including sound, objects, and humans, all of which are capable of producing effects on one another, thus shaping literacies and literate learners.…”
Section: Talk Discourse and Noise In Schooled Bodiesmentioning
confidence: 99%
See 1 more Smart Citation